Effect of atmospheric particulate matter on the functional state of mitochondria - Elena V. Kondratyeva; Tatyana I. Vitkina (Russian Open Medical Journal)
The health risks associated with outdoor air pollution are of global concern. Atmospheric air pollution negatively affects a number of key aspects of human health, including the functioning of the respiratory, cardiovascular and central nervous systems, but many issues remain unresolved about the relationship between atmospheric air pollution and the development and course of pathologies. The review analyzes data from Russian and foreign sources on the effect of atmospheric particulate matter on the functional state of mitochondria. The effect of air pollution on structural changes in mitochondria, ATP synthesis, production of reactive oxygen species, damage to mitochondrial DNA, and mitochondrial membrane potential has been shown. The data presented in the review indicate the need for further studies of the functional state of mitochondria under the impact of solid particles in atmospheric air.